Manipulation of gut microbiota using acacia gum polysaccharide - Rawi, Muhamad Hanif; Abdullah, Aminah; Ismail, Amin; Sarbini, Shahrul Razid (American Chemical Society, 2021)
Acacia gum (AG) is a branched-polysaccharide gummy exudate that consists of arabinose and galactose. The traditional practice in African-Middle Eastern countries uses this gum as medicine. Traditional use of AG is to treat stomach disease, which can be a potential functional food. In this research, commercially available AG from Acacia senegal and Acacia seyal was investigated as the prebiotic. The experiment employed a pH-controlled in vitro colon model inoculated with human fecal microbiota to mimic the human colon. Fermentation samples at 0, 6, 12, and 24 h were brought for short-chain fatty acid (SCFA) analysis using high-performance liquid chromatography and bacterial enumeration via fluorescent in situ hybridization. Results showed that AG significantly promotes Bifidobacteria proliferation similar to fructo-oligosaccharides (FOS) while inhibiting the Clostridium histolyticum group, commonly associated with gut dysbiosis. Acetate, propionate, and butyrate showed a similar trend to FOS (p > 0.05). The AG shows potential against gut dysbiosis, as it promotes gut-probiotics, through modulation of microbial population and SCFA production, especially butyrate.